Method of using anticholinesterase preparations in combination with the method of direct electrical stimulation at peripheral nerve neuropathies. Three cases report - I. A. Meshcheryagina; O. S. Rossik (Acta Biomedica Scientifica, 2014)
An anticholinesterase preparation was introduced in 3 patients 30 minutes before direct electrical stimulation with low-intensity current in order to reduce treatment time, to increase muscle tension and to decrease sensitive disorders in the zone of innervation of the brachial plexus and peripheral nerve. 1,0 ml of 0,05% proserin solution was injected. Once reaching maximum concentration in blood proserin allowed to achieve potentiating the effect of electrical stimulation, increasing patient's muscle strength and independent muscle contractions, as well as 0,18 mV, on the average, increasing voluntary activity of the muscles tested according to EMG results which corresponds to 37-45 % of physical activity of the tested muscle group. The proposed method allowed to reduce treatment periods, to regress focal symptoms, to increase muscle tension and to decrease sensitive disorders in the zone of peripheral nerve innervation.